Filmic representation of Labour Law during the Franco Regime - Escribano Gutiérrez, Juan (Cuadernos de Historia del Derecho, 2016)
The world of labour has not had a wide representation along the history of cinema. Nevertheless, an analysis of the films that have dealt with that subject direct or indirectly during a certain historical period can help to throw important conclusions about the ways in wich this important human activity was socially and juridically faced. Specifically, the analysis of the cinema production during Franco’s regime makes us possible to contemplate such important aspects as the incorporation of women to the work forces, the unions backlash or the crisis of employment in the first period of Franco’s regime.
Keywords: Labour; history; proletariat; image; Falange; Franco regime; transition to democracy